LncRNA mediated metabolic reprogramming: the chief culprits of solid tumor malignant progression: an update review - Kun Fang; Huizhe Xu; Shuai Yuan; Xiaoxi Li; Xiaoyu Chen; Xiushi Fan; Xiaoxin Gao; Lu Zhang; Shulan Sun; Xudong Zhu (Nutrition & Metabolism)
Abstract Metabolism reprogramming (MR) is one of the top ten hallmarks of malignant tumors. The aberrant activation of MR has been recognized as a critical contributory factor to the malignant progression of solid tumors. Moreover, various long non-coding RNAs (lncRNAs) are implicated in the aberrant activation of MR in solid tumor cells. Therefore, in this review, we mainly focus on summarizing the functional relevance and molecular mechanistic underpinnings of lncRNAs in modulating MR of solid tumors by targeting glucose metabolism, lipid metabolism, affecting mitochondrial function, and regulating interactions between tumor and non-tumor cells in tumor microenvironment. Besides, we also underscore the potential for constructing lncRNAs-centered tumor metabolic regulation networks and developing novel anti-tumor strategies by targeting lncRNAs and abnormal MR. Ultimately, this review seeks to offer new targets and avenues for the clinical treatment of solid tumors in the future.